Legal basis information security states of broadcasters - Кононова, О. В. (Theory and practice of jurisprudence, 2016)
Problem setting. The need for the emergence and development of the law of information security explained by the need to organize social relations that occur between individuals and legal entities, citizens’ associations and public authorities for creating, collecting, receiving, storage, use, distribution, security, information security. For the implementation of public policy at the National Security and Defense Council of Ukraine has interdepartmental committee on information policy and information security, which is an advisory body. Meanwhile, freedom of information is not only determining natural right (freedom) rights, it is the basis of building a free information society, which can not happen without the full freedom of information their citizens. Analysis of recent publications and sources. Research practical implementation of business entities in different sectors of the national economy have been the subject of many studies such as lawyers: A. M. Vinnyk, D. V. Zadyhaylo, G. L. Znamenskii, V. K. Mamutov, V. M. Pashkov, A. P. Podtserkovnyy, V. A. Ustimenko, V. S. Shcherbina more. However indication scientists did not pay enough attention to the peculiarities of economic activities and broadcasting organizations providing information security in carrying out such activities. Formulation purposes. The purpose of this paper is to organize social relations that occur between individuals and legal entities, public associations and public administration for creating, collecting, receiving, storage, use, distribution, security, information security, and studies of private and public andlegal rules aimed at streamlining public relations information security. 2 The main material. One way of ensuring information security in the area of broadcasting is to provide public information policy by creating custom reports and reports on the most important measures in this area of the state, of direct television and radio streams on the activities of public bodies operating information policy of systematic problem, thematic TV and radio programs that require processing procedure for funding NGOs broadcasting lighting activities of state and local governments. Prospects for the state information policy in Ukraine broadcasting primarily be related to the development of international information, the formation of an international information space. The basic principles of broadcasting regulation enshrined fundamental documents of the European institutions. For the EU, this principle is the freedom to provide services, and for the Council of Europe - the right to freedom of expression. Questions mechanisms of information exchange between state and society and between the public and private media for Ukraine in recent years is relevant. This refers to the need to introduce the concept of a unified state propaganda and increased state control over the circulation of information, the return of state capacity sufficient to inform the public about their goals and intentions. Conclusion. Thus, a key element of the concept of "information security" is national interests that unite these components of national security: 1) avoid potential interference with the information system and the information stored therein; 2) prevent the manifestation of freedom of speech and access to information; 3) preventing the spread of media cult of violence, cruelty, pornography; 4) prevent computer crime and computer terrorism; 5) to prevent the disclosure of information of state or other provided by law, secret and confidential information that is publicly owned or directed at the needs and national interests of society and the state; 6) prevent attempts to manipulate public opinion, including through dissemination of false, incomplete or biased information; 7) preventing the disclosure of information resources, violation of the integrity or malfunction of the device.